2016
DOI: 10.1002/2016gl070021
|View full text |Cite
|
Sign up to set email alerts
|

Modern deposition rates and patterns of organic carbon burial in Fiordland, New Zealand

Abstract: Fjords are disproportionately important for global organic carbon (OC) burial relative to their spatial extent and may be important in sequestering atmospheric CO2, providing a negative climate feedback. Within fjords, multiple locally variable delivery mechanisms control mineral sediment deposition, which in turn modulates OC burial. Sediment and OC sources in Fiordland, New Zealand, include terrigenous input at fjord heads, sediment reworking over fjord‐mouth sills, and landslide events from steep fjord wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 41 publications
2
27
3
Order By: Relevance
“…Fjord‐head deltas, like many other deltas, have long been proposed as traps for coarse particles due to reduced flow energy (Gibson & Hickin, ; Orton & Reading, ). The coarse‐grained particles found at all deltaic stations in this study, in contrast with the fine‐ grained particles in fjord sediments (Ramirez et al, ), indicated that the Gaer Arm fjord‐head delta is comparable to other fjord‐head deltas in trapping the majority of coarse particles in a fjord system. The ability of fjord‐head deltas to trap coarse‐grained sediments has been more attributed to the presence of particle‐trapping vegetation growth on the delta, rather than direct deltaic deposition (Walling et al, ).…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Fjord‐head deltas, like many other deltas, have long been proposed as traps for coarse particles due to reduced flow energy (Gibson & Hickin, ; Orton & Reading, ). The coarse‐grained particles found at all deltaic stations in this study, in contrast with the fine‐ grained particles in fjord sediments (Ramirez et al, ), indicated that the Gaer Arm fjord‐head delta is comparable to other fjord‐head deltas in trapping the majority of coarse particles in a fjord system. The ability of fjord‐head deltas to trap coarse‐grained sediments has been more attributed to the presence of particle‐trapping vegetation growth on the delta, rather than direct deltaic deposition (Walling et al, ).…”
Section: Discussioncontrasting
confidence: 59%
“…In contrast, the five subtidal surface‐grab samples (F8–F12) showed large variation in median grain size varying between 1250.41 and 45.36 μm, with a consistent decreasing trend in grain size from upper (F8) to lower (F12) stations (Figure S4). It is clear that fjord sediments in the deeper stations have a much finer grain size average (9.43 ± 5.09 μm) (Ramirez et al, ) than found in the Gaer Arm fjord‐head delta.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Differences in the burial of C org in large river‐dominated continental margins are primarily controlled by changes in the terrestrial sediment supply (Syvitski et al, ), SARs (Allison et al, ), hydrodynamics (Tesi et al, ), and biological processes (Ramirez et al, ). There were dramatic alterations in the transfer of suspended particles from the land to the sea between the 1950s and 2015, associated with river damming and cultivated land changes in the drainage basin, and the particle loads and amounts of terrestrial C org to the YRE decreased by >60% and >86%, respectively (Figure S2; Li et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%